Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2020)
This issue of KIU Journal of Humanities touches on Development Studies, Social Psychology, Religious Studies, Language and Literary Studies, as well as Entrepreneurship and Agricultural Economics. The first part of the Journal addresses issues in Development Studies such as internal security and national development, public service delivery, global pandemic and development, crisi of nation building, globalization, imperialism and so on. It is revealed in one of the papers that the emergency of the virus in some towns and cities in Nigeria calls for serious attention. The paper therefore, recommends among others, the isolation or restriction of movement of suspected cases within the facility, banning of visits to detention facilities, decongestion of correctional facilities and setting up of disease prevention and control units in correctional or detention facilities across the country in order to stem the spread of the virus to correctional facilities. In the second section which centers on Social and Educational Psychology, various factors which have impacts upon students, which may include emotional intellegence, study habit, peer groups, emotional sentiments, and mental hygiene etc. are examined. One of these papers reveals that that Narrative Exposure Therapy (NET) had no effects difference on participants’ psychological trauma symptoms across age group. Based on the findings of this study, it is recommended among others; that there is need for more psychological studies to be conducted amongst children at internally displaced camps so that both young and old would have gone through the therapy. In addition, future studies should be done for children in the Internally Displaced Persons’ camps for the purpose of comparing between children, adolescents and old that have gone through the therapy. In Section Three, literary works of Ola Rotimi, Sam Ukala, Usimi Taiwo, as well as Mongo Béti and Ahmadou Kourouma are x-rayed. Also, language and tenor of President Muhammadu Buhari’s Speech on covid-19 pandemic to the general populace in Nigeria are examined in one of the papers. It is revealed that the President used declarative sentences as a way of giving information to the audience and also for creating a natural conversational phenomenon between the president and the listeners so that the general populace could understand the intended message(s). The study concludes that examining nationwide broadcast given during this pandemic through the language use, metadiscourse elements, and tenor of discourse aid comprehension of the intended message being passed across to the audience. In part four, some importance issues in Religious Studies are examined. One of the papers highlights the Islamic perspectives of what is called child spacing or control. The paper rejects the idea of child spacing or birth control based on western model and argues in favour of child spacing from the Islamic point of view based on ‘azl’ and the Islamic model of child rearing and weaning as supported by relevant Qur’anic verses. Section Five examines salient issues in Entrepreneurship and Agricultural Economics. Some of these include agricultural credit loans, teaching business education and food technology. It is disclosed in one of the papers there is a positive but insignificant relationship between intangible assets and profitability of Nigeria’s deposit money banks. Therefore, organisations should invest significantly in intangible assets in order to boost profitability. In all, this edition of KIU Journal of Humanities features many empirical and theoretical based articles. Each of them seeks to profer solutions to one social and management problem or the other. Therefore, there is something to learn by every reader of this issue.